Breastfeeding and Related Factors in Afrodescendant Women From Cartagena, Colombia - Shyrley Díaz Cardenas; Sthefanie del Carmen Perez Puello; Luis Antonio Buelvas Montes (Association of Support to Oral Health Research (APESB), 2022)
Objective: To describe practices and related factors to breastfeeding in afrodescendant women from Cartagena de Indias city, Colombia. Material and Methods: Cross-sectional study conducted between 2016 and 2017 in 548 mothers who had under 5 years children from afrodescendant communities. A self-reported questionnaire was applied, asking for sociodemographic variables, breastfeeding time and exclusive breastfeeding, family support and factors related to this practice. Data were analyzed  by descriptive statistics and risk estimation by Odds Ratio (OR). Results: Most mothers were young adults (89.8%), having high scholar level (55.2%), family support and they were associated to the public health system. The prevalence of breastfeeding and exclusive breastfeeding during the first 6 months was 91.6% and 80.4%, respectively. Breastfeeding and exclusive breastfeeding practice were associated with mother's age (OR = 3.24, 95% CI= 1.80-5.8) and low mother's educational level (OR = 3.24, 95% CI= 1.8-5.8). Finally, no breastfeeding and the fact of not being performed exclusively was associated with no mother nipples examination, and not or insufficient information supplied about this issue. Conclusion: Breastfeeding practice was associated with mother's age and her educational level as well as with poor preparation to start this practice. Although its prevalence was high, it is necessary to implement policies within health system to encourage its practice and provide measures to solve problems during their development in mothers from vulnerable communities.